Migration and Human Capital: The Effect of Education on the Qualified Employment of Venezuelan Immigrants in Peru - Melo-Vega-Angeles, Oscar; Chuquillanqui-Lichardo, Bryan; Gomes Haensel Schmitt, Valentina (Migration Letters, 2023)
This study analyzes the impact of Venezuelan immigrants’ human-capital on their occupational choice in Peru, in terms of job qualifications. Cross-sectional data were sourced from the National Survey to the Venezuelan Population in Peru, using ordered probit models for 2018 and 2022. The results show that immigrants with university education or previous job experience are overeducated for jobs requiring university education, in the Peruvian labor market, for both years, since they are more likely to obtain jobs with technical education requirements, the intensity of the phenomenon reduced in 2022. The study verifies the Venezuelan immigrants’ overeducation in the Peruvian labor market.